2023
DOI: 10.1055/a-2010-2452
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Metabolic Score for Insulin Resistance and Hypertension in Adults: A Meta-Analysis

Abstract: The metabolic score for insulin resistance (METS-IR) is a recently developed parameter for screening of metabolic disorder. However, the association between METS-IR and risk of hypertension in general adult population remains not fully determined. A meta-analysis was therefore performed. Observational studies evaluating the association between METS-IR and hypertension in adults were retrieved by searching PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Moreover, METS-IR had higher predictive ability for hypertension compared to other IR indices, including HOMA-IR, TyG, and TG/HDL-C [ 52 ]. A meta-analysis of 8 observational East Asian studies revealed that the highest versus lowest category of METS-IR was associated with a 67% greater risk of hypertension and each unit increase in METS-IR was associated with a 15% higher hypertension risk [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, METS-IR had higher predictive ability for hypertension compared to other IR indices, including HOMA-IR, TyG, and TG/HDL-C [ 52 ]. A meta-analysis of 8 observational East Asian studies revealed that the highest versus lowest category of METS-IR was associated with a 67% greater risk of hypertension and each unit increase in METS-IR was associated with a 15% higher hypertension risk [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…METS-IR is known to be associated with various adverse clinical outcomes, including coronary heart disease (CHD) [ 17 ], stroke [ 18 ], diabetes [ 12 ], hypertension [ 19 , 20 ], and CKD [ 21 ]. However, there was no correlation between METS-IR and coronary artery diseases in a case-control study among Iranian patients in the fully adjusted model [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-calorie, high-salt, high-fat, animal protein-rich diets and low fiber intake can alter intestinal barrier function and increase metabolic endotoxemia, reactive oxygen species (ROS), and inflammation. These disturbances contribute to dysfunction of the cardiometabolic system, organ damage, and high blood pressure (24,25).…”
Section: Inflammation and Reactive Oxygen Species (Ros)mentioning
confidence: 99%